El stop motion como contribución en el reconocimiento cultural de las máscaras de la Diablada Pillareña con estudiantes de octavo semestre de la carrera de pedagogía de las artes y humanidades - Altamirano Nieto, Keyla Abigail (2025)
This research project aims to promote the cultural recognition of the masks worn in the “Diablada Pillareña” among eighth semester students in the Pedagogia de las Artes y Humanidades career. Through the use of a mixed methodology, a stop motion animation was proposed to narrate the origin of this masks. The information required was taken from artisans, dancers, and cultural managers, complemented by statistical analysis and interviews. It allowed to have a holistic perspective on the efforts of Píllaro’s community to preserve the cultural heritage of the “Diablada Pillareña”. The study converted the collected narratives into an audiovisual pedagogical resource, showing a significant improvement in the understanding of students of this tradition which can lead to a significant improvement of the knowledge in a graphic and narrative way that can contribute to the preservation of the identity of this tradition.